PENGUATAN EKOSISTEM UMKM MELALUI KOLABORASI PEMERINTAH DAN DUNIA USAHA: MODEL KEMITRAAN DAN MANAJEMEN HUBUNGAN STAKEHOLDER - Yohan Purnawan; Hendri Mayanta; Muhammad Rijal Panjaitan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This report discusses strengthening the MSME ecosystem through collaboration between the government and the business world. The goal is to develop an operational partnership model and a measurable stakeholder relationship management approach, addressing issues related to support fragmentation, market access, financing, and suboptimal coordination. The activities include stakeholder mapping, designing partnership models, and implementing collaborative programs such as market access and quality improvement. The methodology covers needs mapping and assessment, development of SOPs and KPIs, and carrying out the program in the form of trial projects. The main outputs include partnership model documents and a 12-month action plan. Effective collaboration is expected to strengthen the position of MSMEs in the local economic ecosystem.